PENGARUH KUALITAS PELAYAN TERHADAP KEPUASAN KONSUMEN PADA HOTEL GELORA SAMARINDA - Irma Agustina (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
IRMA AGUSTINA, Effect of Service Quality toward Customer Satisfaction At Hotel Gelora Samarinda, (supervised by Mr. Suharno and Mrs. Asnawati).This research aimed to determine whether there was a significant and positive effect beetwen service quality on customer satisfaction at Gelora Samarinda Hotel. The independent variables in this research was Tangibles, Reliability, Responsiveness, Assurance, and Emphaty. While the dependent variable is customer satisfaction. The research was conducted at Hotel Gelora Samarinda, and respondents as many as 100 people.This research used a questionnaire which was distributed to 100 respondents. The results of questionnaire were analyzed using multiple linear regression. From questionnaire data tabulation, the results of this research indicate that the Tangibles, Reliability, Responsiveness, Assurance, and Emphaty have a positive and significant impact toward Customer Satisfaction at Hotel Gelora Samarinda. Based on the value of the coefficient of the research (R), that the fifth of independent variables in this research affect Costumer Satisfaction as much 59.40 %.